Unilateral acts of states in public international law - Saganek, Przemysąw (Queen Mary studies in international law., 2016)
In Unilateral Acts of States in Public International Law Przemysław Saganek discusses one of the most important sources of States' obligations in international law. He analyzes in a critical way the classical catalogue of unilateral acts comprising: promise, waiver, recognition and protest. He convincingly proves that this list is misleading as it oversees several important acts of States. On the other hand, several classical acts do not necessarily give rise to legal effects or are not necessarily unilateral. The author undertakes a thorough analysis of several types of acts, showing their similarities and dissimilarities. He concludes that the group category of 'unilateral acts' covers such diverse elements that they could be hardly codified in a single set of rules.